Comparison between direct use and PLGA nanocapsules containing drug of traditional Chinese medicine, Tiaojing Zhixue, in treatment of dysfunctional uterine bleeding - Han, Jun; Wang, Xianghua; Lv, Wei; Tian, Rui Yun; Guan, Leilei (Cellular and Molecular Biology, 2021)
Dysfunctional uterine bleeding is menstrual bleeding in abnormal volume, duration, or time, and it is a common problem in women. A wide range of drug therapies, with varying efficacy, is available for women with dysfunctional uterine bleeding. The use of herbal and traditional medicine is one of the ways to treat this disease, which has fewer side effects than chemical drugs. On the other hand, these medicines have less effect on treatment than chemical drugs. Therefore, increasing their effectiveness in the treatment of diseases has always been important. For this purpose, in this study, a comparison was done between direct use and PLGA nanocapsules containing Tiaojing Zhixue, in the treatment of dysfunctional uterine bleeding. First, PLGA nanocapsules containing Tiaojing Zhixue were synthesized by the electrospray technique. Then 80 women with dysfunctional uterine bleeding were treated with this medicine. These people were divided into two groups of 40 people. The first group was treated with 20mg of Tiaojing Zhixue and the other group was treated with PLGA nanocapsules containing Tiaojing Zhixue for eight months. The duration and frequency of bleeding from one month before the start of treatment and during the eight months after the start of treatment (second, fourth, and eighth month) were assessed in two groups. The two groups were homogeneous in terms of mean frequency of bleeding and mean duration of bleeding before starting treatment. The positive response in the PLGA nanocapsules treatment group (75%) was higher than the direct use drug treatment group (42.5%) (P < 0.01). The rate of side effects was the same in each group. Due to the effectiveness of PLGA nanocapsules in the treatment of dysfunctional uterine bleeding and the lack of side effects, it can be considered as an alternative medicine for the treatment of this disorder.